Lyophilized nano-liposomal system for red onion (Allium cepa L.) peel anthocyanin: Characterization, bioaccessibility and release kinetics - Sahin, Oya Irmak; Dundar, Ayse Neslihan; Uzuner, Kubra; Parlak, Mahmud Ekrem; Dagdelen, Adnan Fatih; Saricaoglu, Furkan Turker (Elsevier, 2023)
In recent years, there has been extensive research on valorization of food wastes and a growing interest in nano-liposomal systems for food applications. This paper discusses the case of phosphatidylcholine base-dnanophytosomes loaded with anthocyanins extracted from red onion (RNPs) to overcome the bio-stability during digestion. The characterization of lyophilized RNPs in terms of entrapment efficiency, particle size, poly-dispersity index (PDI), zeta-potential, morphological properties, in vitro bioaccessibility and release kinetics were investigated. Entrapment efficiency was determined as 78.63% with lowest particle size (177.73 nm) and PDI value (0.45) and non-dense spherical microstructure for RNP6 (red onion peel anthocyanin extract: soybean phosphatidylcholine at 1:6 ratio). Apart from the particle size, entrapment efficiency was determined higher than 75%, which indicates good entrapment. Additionally, from the cumulative release of RNPs concluded as a successful nano-structure with a two-fold increase in intestinal medium. However, poor Carr index and Hausner ratio suggest some limitations of the current nanoliposomes process which could be further improved. Red onion peel wastes, which are typically discarded, can serve as excellent sources of anthocyanins, and its preparation to nanophytosomes could be used as functional food ingredient or food supplements.
Keywords: Anthocyanin; Red onion peel; Phytosome; Nanocarrier; Bioactive compounds; In vitro bioaccessibility